Motivation Analysis of Online Green Users: Evidence From Chinese “Ant Forest” - Chen, Bo; Feng, Yi; Sun, Jinlu; Yan, Jingwen (Frontiers in Psychology, 2020)
Environmental protection activities based on digital technology have cultivated many online green users (OGUs) and may become a critical means to combat global climate change. This paper explores individuals’ motivation to participate in online environmental protection activities and whether the activities have significantly increased individuals’ intention to participate in global collaboration on climate change. Taking Ant Forest as an example, this paper first summarized 14 trigger reasons for users’ participation in online environmental protection activities through interviews, then surveyed 600 OGUs through questionnaires, and studied the behavioral motivation from the four dimensions of environmental awareness, social motivation, online immersion, and global cooperation intention by using a structural equation model. The study found that both environmental awareness and social motivation had significant positive promotional effects on OGUs’ online immersion, and environmental awareness was higher than social motivation. Environmental awareness as a long-term motivation is conducive to the achievement of long-term climate goals, and social motivation is focused on short-term entertainment functions. There is a significant positive interactive relationship between environmental awareness and social motivation under the effect of digital technology, which jointly promote the improvement of OGUs’ online immersion, and online immersion is conducive to enhancing OGUs’ global cooperation intention. This study demonstrated that digital technology can effectively improve individuals’ intention to protect the environment, and found a means to quickly identify the best OGUs (most willing to participate in global cooperation), which provided a new opportunity to inspire greater public participation in the global action against climate change.